2023
DOI: 10.9734/ijecc/2023/v13i71865
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability of Farmers to Climate Change in Central Dry Zone of Karnataka

Abstract: Changing climatic parameters will have a huge effect on life and nature. Climate change will be best viewed through the increase in temperature, melting of ice and rapid rise in sea level. Such changes causes severe problems to human beings and other forms of life. Vulnerability to climate change is intimately related to poverty, as the poor are least able to respond to climatic stimuli. Further, certain regions of the world are more harshly affected by the effects of climate change than others. With this back… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
0
0
0
Order By: Relevance
“…Overall vulnerability of paddy farming households in North Aceh was more vulnerable to climate change compared to Aceh Besar because the vulnerability value of paddy farming households in Aceh Besar was 0.44 and North Aceh was 0.45. Shankara et al [18] revealed that the exposure of farmers to climate change, rainfall and temperature were selected and the majority of farmers were severely exposed (0.822) and sensitive (0.894) to climate change with lower adaptive capacity (0.576) between the year 2013-2017. It showed that, 0.186, 0.226, 0.224, 0.220 and 0.241 was the Climate Vulnerability Index (CVI) of Arsikere, Kadur, Tiptur, Chiknayakanahalli and Challakere taluk, respectively.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Overall vulnerability of paddy farming households in North Aceh was more vulnerable to climate change compared to Aceh Besar because the vulnerability value of paddy farming households in Aceh Besar was 0.44 and North Aceh was 0.45. Shankara et al [18] revealed that the exposure of farmers to climate change, rainfall and temperature were selected and the majority of farmers were severely exposed (0.822) and sensitive (0.894) to climate change with lower adaptive capacity (0.576) between the year 2013-2017. It showed that, 0.186, 0.226, 0.224, 0.220 and 0.241 was the Climate Vulnerability Index (CVI) of Arsikere, Kadur, Tiptur, Chiknayakanahalli and Challakere taluk, respectively.…”
Section: Review Of Literaturementioning
confidence: 99%
“…while 2.50 per cent were "Highly Vulnerable," indicating a small but critical portion requiring immediate and targeted support. Lastly, none of the respondents fell into the "Not Vulnerable" category [8][9][10][11][12].…”
Section: Co-efficient Of Correlationmentioning
confidence: 99%
“…Crops, fish, and livestock productivity may increase or decrease based on agro-climatic zones (ACZ) and the severity of impacts [10][11][12][13]. For instance, increasing soil salinity is evidenced in arid regions [14], whereas dry zones are vulnerable to drought with increased temperature [15,16], and wet regions are expected to receive excess and erratic rains, causing floods [17,18]. Moreover, the farmer's vulnerability to climate change impacts and their level of adoption varied significantly based on their level of education, farming experience, farm size, and annual income.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies highlighted different climate change perceptions, their validation with meteorological data, and adoption strategies by farmers. Reduction in yield and income due to climate change is perceived as a significant constraint by farmers in the dry eastern region of Karnataka, India [15]. Change in the monsoon pattern or initiation and termination of rainfall due to climate change is perceived in most cases by farmers [20,38].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation